Determinants of technical efficiency in cotton production in the southern cotton growing zone of Nigeria: A stochastic production frontier approach - OLATIDOYE, MUYIWA SUNDAY; ALIMI, TAIWO; AKINOLA, ADEBAYO AKINBOYE (Society for Indonesian Biodiversity & Universitas Mulawarman, Samarinda, Indonesia, 2018)
Abstract. Olatidoye MS, Alimi T, Akinola AA. 2018. Quality assessment of the physico-chemical properties of vermiwash produced from different sources during successive storage periods. Asian J Agric 2: 58-63. The study investigated on socio-economic factors and estimated the technical efficiency indices and factors influencing technical efficiency of the sampled cotton farmers in the Southern Cotton growing zone of Nigeria. A multistage sampling technique was employed to select a total sample of 300 cotton farmers. The study made use of only primary data which was collected through the aid of a well-structured questionnaire. The data were analyzed using descriptive statistics and stochastic frontier production parametric model. The results of the descriptive statistics showed that majority (83%) of the cotton farmers in the study area were males while the mean age of the respondents was 49 years. The average household size was 8 persons per household and majority (69%) of the respondents had formal education. Majority of the respondents (59%) had no access to credit facilities while majority (80.4%) of the cotton farmers had reasonable years of experience ranging between 11 and above in cotton production. Furthermore, the study found that the technical efficiency of the farmers range from 0.35 and 0.99 with a mean of 0.79. This indicates ample opportunity for farmers to increase their productivity through improvement in their technical efficiency. Seed, fertilizer, pesticides and farm size were found to be statistically significant and positively related to farmers’ output while education, credit, extension contact and farming experience of the respondents negatively influenced farmers’ technical inefficiency. The farmers therefore need to increase their output through more intensive use of seed, land, pesticides and fertilizers.